2016
DOI: 10.2214/ajr.15.15032
|View full text |Cite
|
Sign up to set email alerts
|

Performance of DWI in the Nodal Characterization and Assessment of Lung Cancer: A Meta-Analysis

Abstract: Current evidence suggests that DWI is beneficial in the nodal assessment of patients with lung cancer, and it is necessary to conduct high-quality prospective studies regarding the use of DWI in detecting metastatic lymph nodes of lung cancer to determine its true value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…For MRI alone, the sensitivity to detect nodal disease was 67% (95% CI 56% to 77%). In their 2016 meta-analysis, which included 1122 participants, Peerlings et al 18 reported that thoracic MRI had 87% (95% CI 78% to 92%) sensitivity for per-patient nodal staging in lung cancer, although Shen et al 19 reported a sensitivity of 68% (95% CI 63% to 73%), which is more consistent with our findings. Indeed, in a study of 113 participants with a histological reference standard, Kim et al 76 reported that morphological MRI observations had a per-patient sensitivity of 68% and a per-nodal station sensitivity of 53%, again very similar to our findings.…”
Section: Diagnostic Accuracysupporting
confidence: 89%
See 2 more Smart Citations
“…For MRI alone, the sensitivity to detect nodal disease was 67% (95% CI 56% to 77%). In their 2016 meta-analysis, which included 1122 participants, Peerlings et al 18 reported that thoracic MRI had 87% (95% CI 78% to 92%) sensitivity for per-patient nodal staging in lung cancer, although Shen et al 19 reported a sensitivity of 68% (95% CI 63% to 73%), which is more consistent with our findings. Indeed, in a study of 113 participants with a histological reference standard, Kim et al 76 reported that morphological MRI observations had a per-patient sensitivity of 68% and a per-nodal station sensitivity of 53%, again very similar to our findings.…”
Section: Diagnostic Accuracysupporting
confidence: 89%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Many have combined multiple cancer types in one single meta-analysis. [9][10][11]13,14,16,17 Those meta-analyses considering the staging of only lung cancer have limited themselves to the detection of bone 12,15 or nodal [18][19][20] metastasis. No meta-analysis has considered colon cancer in isolation, and the largest study to date recruited just 20 participants.…”
Section: Existing Literature On the Diagnostic Accuracy Of Wb-mri In mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that DWI has great clinical application value and potential in the differential diagnosis of lung cancer (20). Shen et al (21) suggested that DWI is beneficial in the nodal assessment of patients with lung cancer. Tumor cellular densities increase due to the increase in DWI signals, and the signal intensity and distribution of DWI can represent the number of cancer cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…25) Recently, the diagnostic capability of MRI has developed and two articles of meta-analysis reported that DWI was effective for the evaluation of N factor of lung cancer. 26,27) Meta-analysis of the MRI by Peerlings et al 26) revealed high diagnostic capability that the sensitivity was 0.87, the specificity 0.88 for nodal assessment in the non-small-cell lung cancer.…”
Section: Resultsmentioning
confidence: 99%